Effective Invigilation as a Panacea for Examination Malpractices among Students of Tertiary Institutions in Nigeria (Global Journal of Human-Social Science, 2014)
Examination by whatever name it is called is very important to educational system as air is important to life. Examination serves very many useful purposes at any education system and level. The useful purposes of examination at any education system can be marred by its conduct especially if it allowed for examination malpractice. Examination malpractice is one of the plagues that be devilled tertiary institutions in Nigeria. Examination malpractice in the tertiary institutions is on the increase daily taking different forms and dimensions. However, the menace thrives well when examination invigilation is very slack. Examination invigilation rests solely on invigilators and other stakeholders in the conduct of examinations invigilation. Therefore, examination invigilators determine the quality of examination invigilation. Effective invigilation of examination can only be made possible through effective invigilators who will reduce if not totally eradicate the menace of examination malpractice and this is the thrust of this paper.
Keywords: education (al) system; tertiary institution; examination malpractice; examination invigilation; effective examination invigilation; examination invigi